The politics of liturgy between tradition and modernity in South Africa - J. Rossouw (Acta Theologica)
How can Catherine Pickstock’s statement that “Traditional communities governed by liturgical patterns are likely to be the only source of resistance to capitalist and bureaucratic norms today” be interpreted in contemporary South Africa in such a way that justice and recognition are upheld? I propose to answer this question in the following four steps. First, the notion of liturgy with reference to politics will be briefly discussed. Second, modernity as an ongoing liturgical disruption, in general, and more particularly in South Africa will be discussed. Third, South Africa as a country between tradition and modernity will be addressed. In conclusion, some proposals for the facilitation of a liturgical politics in modernity, in general, and in South Africa, in particular, will be made. These proposals will be concerned with a plea for the province, the contemplative church and the contemplative university.